Christian-Jewish relations, 1000-1300 - Abulafia, Anna Sapir, 1952- author. Link
1 online resource (xxiv, 227 pages)
Keywords: "This new and revised edition of Christian-Jewish Relations 1000-1300 expands its survey of medieval Christian-Jewish relations in England, Spain, France and Germany with new material on canon law, biblical exegesis, and Christian-Jewish polemics, along with an updated Further Reading section. Anna Sapir Abulafia's balanced yet humane account analyses the theological, socio-economic and political services Jews were required to render to medieval Christendom. The nature of Jewish service varied greatly as Christian rulers struggled to reconcile the desire to profit from the presence of Jewish men and women in their lands with conflicting theological notions about Judaism. Jews meanwhile had to deal with the many competing authorities and interests in the localities in which they lived; their continued presence hinged on a fine balance between theology and pragmatism. The book examines the impact of the Crusades on Christian-Jewish relations and analyses how anti-Jewish libels were used to define relations. Making adept use of both Latin and Hebrew sources, Abulafia draws on liturgical and exegetical material, and narrative, polemical and legal sources, to give a vivid and accurate sense of how Christians interacted with Jews and Jews with Christians"--